The Effect of Public Service Quality on Community Satisfaction in Districts of Gorom Island, Eastern Seram - Fientje Palijama (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The purpose of this research is to know how far influence quality of public services to community satisfaction at the Gorom Island District Office, East Seram Regency. The method used in this research is descriptive method with a quantitative approach. The population of this research is 50 people. Methods of data analysis using simple linear regression analysis, Pearson correlation and coefficient of determination using SPSS 22.0 for windows. The results showed that 1). The quality of public services has a positive effect on consumer / community satisfaction76.9%, meaning that the higher the quality of the services provided, the higher the customer satisfaction. Vice versa, if the lower the quality of service provided, it will decrease by one point, then the consumer / community satisfaction will decrease by 0.769 or 76.9%. 2).From the tests carried out, it is obtained The coefficient of determination is 63.5% of customer / community satisfaction is influenced by the quality of public services, while the remaining 36.5% of customer / community satisfaction is influenced by other variables not examined in this study.  Keywords : Quality of Public Services, and Consumer / Community Satisfaction